2022
DOI: 10.5812/jjnpp-122155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aloe vera as a Natural Pharmaceutic in Mouthwashes: A Narrative Review

Abstract: Context: Mouth rinses have been recognized as the main adjuvant or primary treatment to address many issues relating to dentistry. Previous studies have investigated the anti-inflammatory, anti-arthritic, anti-viral, antioxidant, anti-fungal, and anti-bacterial effects of Aloe vera. Recently, Aloe vera has been applied to treat several dental and oral conditions. Methods: Official web pages, such as Scopus, PubMed, and Microsoft were searched for collecting the required data using the keywords Aloe vera, Aloe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Aloe barbadensis miller is a botanical name of Aloe vera [27]. Aloe vera belongs to the Liliaceae family with mucilaginous tissue in its leaf's center [28]. The Aloe vera plant has anti-fungal, anti-inflammatory, antioxidant, immune-modulating, and anti-bacterial properties [17,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe barbadensis miller is a botanical name of Aloe vera [27]. Aloe vera belongs to the Liliaceae family with mucilaginous tissue in its leaf's center [28]. The Aloe vera plant has anti-fungal, anti-inflammatory, antioxidant, immune-modulating, and anti-bacterial properties [17,28].…”
Section: Discussionmentioning
confidence: 99%
“…Aloe vera belongs to the Liliaceae family with mucilaginous tissue in its leaf's center [28]. The Aloe vera plant has anti-fungal, anti-inflammatory, antioxidant, immune-modulating, and anti-bacterial properties [17,28]. Studies have reported the anti-inflammatory effect of Aloe vera, where the gel exerts its anti-inflammatory property through inhibition of COX2, prostaglandins, bradykinins, TNF-α, IL-1β, and extracellular signal-regulated kinase pathway [28].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the patent literature has described the antioxidant, anti-gingivitis, and anti-inflammatory activities of medicinal plant extracts used to develop technologies for treating periodontal disease. Among the medicinal plants mentioned, the following stand out: Zingiber ginger and Alpine officinarum [112], Pepper nigrum, Olea europae [113], Lycium barbarum [114], red tea [115], Acacia nilotica (L.) Delile [116], Aegiceras corniculatum [117], Calendula officinalis [118], tea tree oil and Aloe vera [119], Triphala, Ayurvedic medicinal herbal formulations [120], Ficus deltoidea [121], Arctium lappa, Zataria multiflora and Echinacea purpurea [122], Pistacia lentiscus L. [123], Curcuma longa [124], Nigella sativa [125], and Chrysopogon zizanioides [126].…”
Section: Other Compound-related Patents In Periodontal Diseasesmentioning
confidence: 99%
“…In adddition to mouthwash type, this study also looked at mouthwash quantity to be used. 8 To develop a herbal mouthwash employing the herbs Azadirachta indica, Ocimum tenuiflorum and Clinacanthus nutans that would be more effective and environmentally friendly. Mechanical plaque control is less technically complex than chemical plaque reduction techniques, such as mouthwashes.…”
Section: Introductionmentioning
confidence: 99%